2019
DOI: 10.3390/robotics8030080
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Compliance Properties of an Industrial Robot with the Mozzi Axis Approach

Abstract: In robotic processes, the compliance of the robot arm plays a very important role. In some conditions, for example, in robotic assembly, robot arm compliance can compensate for small position and orientation errors of the end-effector. In other processes, like machining, robot compliance may generate chatter vibrations with an impairment in the quality of the machined surface. In industrial robots, the compliance of the end-effector is chiefly due to joint compliances. In this paper, joint compliances of a ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…In particular, the authors investigated the possibility and performance of replacing a conventional weighting device with a vision on inspection system. The paper [18] focuses at robot compliance modeling for achieving a compensation of small position and orientation errors of the end-effector as well as reducing chatter vibrations. In this paper, joint compliances of a serial six-joint industrial robot are identified with a novel modal method making use of specific modes of vibration dominated by the compliance of only one joint.…”
Section: Advances In Italian Roboticsmentioning
confidence: 99%
“…In particular, the authors investigated the possibility and performance of replacing a conventional weighting device with a vision on inspection system. The paper [18] focuses at robot compliance modeling for achieving a compensation of small position and orientation errors of the end-effector as well as reducing chatter vibrations. In this paper, joint compliances of a serial six-joint industrial robot are identified with a novel modal method making use of specific modes of vibration dominated by the compliance of only one joint.…”
Section: Advances In Italian Roboticsmentioning
confidence: 99%
“…The matrices D q and K q are diagonal and independent of the robot configuration q. In particular, the terms of these matrices represent the viscous damping coefficient and the stiffness of each joint around its rotation axis, and they can be identified by means of an impulsive modal analysis of the robot [17,18]. The movement of the tool and its collision with an object in the plane of motion are described in the operational space, so it is necessary to transfer the description of robot dynamics from the joint space to the cartesian space.…”
Section: Model Of Robot Compliancementioning
confidence: 99%
“…Therefore, it is possible to achieve functional redundancy [23], and the robot can perform the same task using different configurations. For example, if the stiffness and inertial properties of the robot are known or experimentally identified [24,25] it is possible to choose a proper configuration so that the kinematic chain of the robot is stiff enough to perform the grinding operation. However, this field of research has only been partially explored.…”
Section: Introductionmentioning
confidence: 99%